Challenges and Learning Needs for Providers of Advanced Cancer Care: Focus Group Interviews with Physicians and Nurses - Tonje Lundeby; Torunn Elin Wester; Jon H?vard Loge; Stein Kaasa; Nina Kathrine Aass; Kjersti St?en Grotmol; Arnstein Finset (Palliative Medicine Reports, 2020)
Background: Implementation of integrated oncology and palliative care improves patient outcomes but may represent a demanding task for health care providers (HCPs). Objective: To explore physicians' and nurses' perceived challenges and learning needs in their care for patients with advanced cancer, and to analyze how these perceptions can provide insight on how to improve care for patients with advanced cancer in an integrated care model. Methods: Residents in oncology, oncologists, nurses, and palliative care physicians were recruited to participate in focus group interviews. Six focus group interviews were conducted with 35 informants. Data were analyzed according to principles of thematic analysis. Results: The discussions in the interviews concerned three broad themes: an emphasis on patients' best interest, perceived as hindered by two sets of barriers; unsatisfactory organizational conditions such as time pressure, lack of referral routines, and few arenas for interdisciplinary collaboration, was perceived as one barrier. The other barrier was related to the appraisal of other HCPs' clinical practices. Participating HCPs expressed in general a positive self-view, but were more critical of other HCPs. Conclusion: Currently, implementation of measures to improve care for patients with advanced cancer appears to be challenging due to cultural and organizational factors, and how HCPs perceive themselves and other HCPs. HCPs' perception of challenges in patient care as not related to themselves (externalization) might be an essential obstacle. Interventions targeting both HCP-related and organizational factors are needed. Particularly important are measures aimed at reducing fragmentation and improving collaboration in care.